1985
DOI: 10.3109/00365518509155270
|View full text |Cite
|
Sign up to set email alerts
|

The Osmoregulatory System and the Renin-Angiotensin-Aldosterone System in Pre-Eclampsia and Normotensive Pregnancy

Abstract: Plasma concentrations of arginine vasopressin (AVP), angiotensin II (A II), aldosterone (Aldo), serum osmolality (Sosm), urine volume (V), and free water clearance (CH2O) were determined in the third trimester of pregnancy, and 5 days and 3 months after delivery in pre-eclampsia (group I), in normotensive pregnancy (group II), and in non-pregnant control subjects (group III). The AVP was the same in the third trimester of pregnancy in groups I and II and did not deviate significantly from the level in group II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…As a consequence, the AVP levels may be not differ ent in patients with PIH and in normal pregnant women, as was noted in our study. Similar findings have been reported by Pedersen et al [22] who have found no significant difference in the plasma concentrations of AVP measured in the 3rd trimester of pregnancy in pa tients with preeclampsia and normotensive pregnancy.…”
Section: Discussionsupporting
confidence: 79%
“…As a consequence, the AVP levels may be not differ ent in patients with PIH and in normal pregnant women, as was noted in our study. Similar findings have been reported by Pedersen et al [22] who have found no significant difference in the plasma concentrations of AVP measured in the 3rd trimester of pregnancy in pa tients with preeclampsia and normotensive pregnancy.…”
Section: Discussionsupporting
confidence: 79%
“…Reports of ANG II plasma concentrations in pre-eclampsia/eclampsia syndrome are not uniform. Normal [9,10] and reduced concentrations [11,12] were found when compared with normotensive pregnancy.…”
Section: Introductionmentioning
confidence: 90%
“…How do such observations in rodent gestation relate to the changes in osmoregulation observed in human pregnancy? Studies in human pregnancy Several groups have measured vasopressin levels in pregnant women, during either cross-sectional and/or serial studies, and in some of these reports PAVp was related to body tonicity either in the basal state or following overnight water deprivation (8,(16)(17)(18). Most author fail to provide the evidence necessary to determine if their assay was reliable.…”
Section: Arginine Vasopressin Release and Thirstmentioning
confidence: 99%